1986
DOI: 10.1111/j.1600-0722.1986.tb01784.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional study of patients treated, with removable partial dentures with special reference to the caries situation

Abstract: Bergman B, Ericson G: Cross-sectional study of padents treated with removable partial dentures with special reference to the caries situation. Scand J Dent Res 1986; 94: 436-42.Abstract -Thirty-four padents provided with removable partial dentures (RPDs) were reexamined after 3 yr. Garies that had developed during the period were analyzed with regard to the following potential caries risk factors: Lactobacilli, Streptococcus mutans, flow rate and buffer pH of paraffin stimulated saliva, oral hygiene and daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
4
17
0
Order By: Relevance
“…This finding corroborates the observations made by RUNDEGREN & ERICSON (7) atid BERGMAN & ERIGSON (24), who concluded that a combinatioti of several tests for estjtnation of caries activity improved the possibility of individual prediction when selecting risk patients. However, there is always uncertainty about the reliability of patients' dietary histories.…”
Section: Discussionsupporting
confidence: 90%
“…This finding corroborates the observations made by RUNDEGREN & ERICSON (7) atid BERGMAN & ERIGSON (24), who concluded that a combinatioti of several tests for estjtnation of caries activity improved the possibility of individual prediction when selecting risk patients. However, there is always uncertainty about the reliability of patients' dietary histories.…”
Section: Discussionsupporting
confidence: 90%
“…The results of studies in which investigators reported on this association are inconsistent, 23,24,25,26,27,28 and most studies in which investigators found a positive association between low stimulated salivary flow rate and dental caries were conducted in children with syndromes such as cleft lip or palate or in hospitalized older adults. 29 Our study results show that a low resting salivary pH was not associated with higher caries experience in the three age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that partial dentures in the mouth increase plaque formation, (Bates & Addy, 1978;Bergman, 1987;Kratochvil, Davidson & Guijt, 1982;Schwalm, Smith & Erickson, 1977;Brill et al, 1977) particularly on tooth surfaces in contact with the partial denture (El Ghamrawy, 1976). An increase in caries has been reported in partial denture wearers (Carlsson, Hedegard & Koivumaa, 1965) and in a study by Bergman and Ericson (1986), 64-5% of the incidence of new caries and 88-5% of recurrent caries occurred on abutment teeth. There are studies, however, that do not support the hypothesis that removable partial dentures increase the likelihood of caries development (Bergman, Hugoson & Olsson, 1977).…”
Section: Introductionmentioning
confidence: 91%